Pengaruh Edukasi Menggunakan Media Poster Digital Interaktif Terhadap Tingkat Pengetahuan Pencegahan Tuberkulosis Pada Siswa Di Smpn 4 Ngaglik - Aulia Chintya; Atik Badi’ah (Journal of Innovative and Creativity (Joecy), 2026)
Tuberculosis (TB) remains a health problem among school-aged children because it can hinder growth and development. A preliminary study at SMPN 4 Ngaglik identified active and latent TB cases, while students' knowledge regarding tuberculosis prevention was still low. Education using interactive digital poster media was selected as an attractive learning medium that suits adolescent characteristics. This study aimed to determine the effect of education using interactive digital posters on the level of knowledge regarding tuberculosis prevention among students at SMPN 4 Ngaglik. This study employed a Pre-Experimental One Group Pretest-Posttest design. A total of 104 seventh-grade students were selected using Stratified Random Sampling. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test. The results showed that most respondents had a moderate level of knowledge during the pretest (60.6%), while the posttest results increased to the good category (77.9%). The Wilcoxon test showed a p-value of 0.000 (<0.05). There was an effect of education using interactive digital posters on the level of knowledge regarding tuberculosis prevention among students at SMPN 4 Ngaglik.